The Role of Acetylsalicylic Acid in the Prevention of Cardiovascular Complications in Patients with Stable Ischemic Heart Disease - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
The historical development and therapeutic significance of acetylsalicylic acid (ASA) have made it one of the most important drugs in modern medicine. From its origins in ancient Sumerian medicine to its synthesis in the 19th century, ASA has evolved from a simple antipyretic agent to a cornerstone in cardiovascular disease (CVD) prevention. The discovery of its antiplatelet properties in the 20th century marked a turning point in the secondary prevention of ischemic heart disease (IHD). Numerous large-scale studies and meta-analyses, including the Antithrombotic Trialists’ Collaboration, ISIS-2, SAPAT, and the Swedish national registry, have demonstrated ASA’s ability to significantly reduce the risk of myocardial infarction, stroke, vascular death, and graft thrombosis. ASA remains a “gold standard” for the prevention of atherothrombotic events and is endorsed by leading international cardiology societies. Recent research also suggests its potential anticancer effects, particularly in reducing colorectal and postmenopausal breast cancer incidence. Despite its proven efficacy, long-term ASA use requires careful monitoring due to the risk of adverse effects, underscoring the need for individualized therapy and continued investigation into safer and more effective regimens.